The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3310/hta10110
|View full text |Cite
|
Sign up to set email alerts
|

Screening for thrombophilia in high-risk situations: systematic review and cost-effectiveness analysis. The Thrombosis: Risk and Economic Assessment of Thrombophilia Screening (TREATS) study

Abstract: Thrombophilia is associated with increased risks of VTE in women taking oral oestrogen preparations and patients undergoing major elective orthopaedic surgery, and of VTE and adverse pregnancy outcomes in women with thrombophilia during pregnancy. There is considerable difference in the magnitude of the risks among different patient groups with different thrombophilic defects. In women who are on combined oral contraceptives, the OR of VTE among those who are carriers of the FVL mutation was 15.62 (95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
1
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(209 citation statements)
references
References 170 publications
5
183
1
20
Order By: Relevance
“…Indeed, the absolute risk of VTE in a woman carrier of FVL mutation is about 0.8% and the absolute risk of obstetric complications is even lower [14]. These conclusions are also supported by a systematic review [13] in which a cost-effectiveness analysis was made and by an economic study [34] both of which did not show a good costeffectiveness ratio of universal screening for thrombophilia. The former two studies refer to the British National Health Service system.…”
Section: Testing Asymptomatic Women For Thrombophiliasupporting
confidence: 60%
See 3 more Smart Citations
“…Indeed, the absolute risk of VTE in a woman carrier of FVL mutation is about 0.8% and the absolute risk of obstetric complications is even lower [14]. These conclusions are also supported by a systematic review [13] in which a cost-effectiveness analysis was made and by an economic study [34] both of which did not show a good costeffectiveness ratio of universal screening for thrombophilia. The former two studies refer to the British National Health Service system.…”
Section: Testing Asymptomatic Women For Thrombophiliasupporting
confidence: 60%
“…Several studies have demonstrated an association between thrombophilia and obstetric complications, such as RPL, unexplained IUFD, preeclampsia, HELLP syndrome, FGR and abruptio placentae [12,13,16,20]. A possible association between thrombophilia and a first pregnancy loss has also been shown [49].…”
Section: Screening For Thrombophilia In Pregnant Women With Previous mentioning
confidence: 99%
See 2 more Smart Citations
“…For other genetic markers, such an association is suspected and discussed controversially, eg, methylenetetrahydrofolate reductase (MTHFR) C677T and/or A1298C and plasminogen activator inhibitor 1 (PAI-1) 4G/5G polymorphisms [1-3, 10, 11, 16, 22, 30, 32, 34, 37, 44]. Results of former studies are conflicting regarding whether the single or combined presence of such genetic mutations may further increase the already very high risk for DVT after major orthopaedic surgery, justifying costly preoperative screening and additional antithrombotic prophylactic measures in these patients [5,6,8,18,20,21,23,29,31,36,[40][41][42][43]. One reason for the conflicting results may be found in the different clinical end points set in the studies varying among venographically diagnosed DVT, clinically symptomatic DVT with or without PE, or symptomatic PE only.…”
Section: Introductionmentioning
confidence: 99%